Acute adductor muscle injury: A systematic review on diagnostic imaging, treatment, and prevention - Gonzales Farrell, S.; Hatem, M.; Bharam, S. (The American Journal of Sports Medicine, 2023)
Background: Controversies remain regarding the diagnosis, imaging, and treatment of acute adductor injuries in athletes.